Streaming de archivos multimedia desde bases de datos Oracle - Jorge Roberto Jova Rodriguez; Alberto Bradshaw Gonzalez; Husseyn Despaigne Reyes (Revista Cubana de Ciencias Informáticas, 2015)
Streaming systems and the advancement of network infrastructure have enabled multimedia content distribution over the Internet, enabling the consumption of these previously without downloading. This paper shows how a system of this type facilitates handling, data integrity and security of media type. The system consists of a web application developed in Java programming language, using Google Web Toolkit technology for creating user interfaces and Oracle to manage audios and videos. Simultaneously, it use Helix Universal Streaming Server 11 to provide information via website, which is retrieved from an instance of Oracle database which stores all data managed by the system. The application development was guided by the Rational Unified Process methodology. The use of different techniques for sending/receiving content to an instance of Oracle database and the use of the technologies exhibited resulted in the development of a streaming system that allows managing and playing multimedia files stored on a database instance Oracle data more efficiently, centrally and securely.